2005
DOI: 10.1029/2004jc002799
|View full text |Cite
|
Sign up to set email alerts
|

Trends and time variability in the northern continental shelf of the western Mediterranean

Abstract: [1] Different works appearing during the last decade show that the western Mediterranean has suffered a temperature and salinity increase during the 20th century. Most of these works analyze long-term trends in Levantine Intermediate Water (LIW) and Western Mediterranean Deep Water (WMDW); those dealing with changes in shallow and coastal waters are very scarce. It is still an open question whether these changes are due to meteorological factors occurring in the western Mediterranean or if they are caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
(67 reference statements)
2
35
1
Order By: Relevance
“…Given that one of our main findings is the temperature dependence of cannibalistic mortality, recruitment variability from year to year may be expected due to slight variations in temperature over the spawning season. In the long term, effects of piscivory on survival may become stronger if average surface tem peratures tend to increase in the Mediterranean as suggested in some studies (Salat & Pascual 2002, Vargas-Yáñez et al 2005.…”
Section: Summary and Broader Potential Implicationsmentioning
confidence: 87%
“…Given that one of our main findings is the temperature dependence of cannibalistic mortality, recruitment variability from year to year may be expected due to slight variations in temperature over the spawning season. In the long term, effects of piscivory on survival may become stronger if average surface tem peratures tend to increase in the Mediterranean as suggested in some studies (Salat & Pascual 2002, Vargas-Yáñez et al 2005.…”
Section: Summary and Broader Potential Implicationsmentioning
confidence: 87%
“…schröder et al (2006) considered that the acceleration of the deep water temperature and salinity trends after 1995 was caused by the influence of the eMT on the WMeD. Pinot et al (2002) reported the progressive disappearance of the Western intermediate Water (WiW) in the balearic sea from 1996 to 1998 and more recently an abrupt decrease of 0.14ºc was observed in the temperature of the newly formed WMDW during the winter of (Font et al, 2007lópez-Jurado et al, 2005) followed by a strong increase in the deep water temperature and salinity in the following winter (smith and bryden, 2007).…”
Section: Time Variability and Time Scales In The Mediterranean Seamentioning
confidence: 99%
“…It is the second representative of Tetraodontidae found after the blunthead puffer, Sphoeroides pachygaster (Müller et Troschel, 1848) (see Hemida et al 2009). The observed increase of the mean annual temperature observed within the last several years in the Mediterranean waters (Béthoux et al 1990, Francour et al 1994, Vargas-Yáñez et al 2005) could possibly explain the recent spreading of Lessepsian migrants from the eastern to the western Mediterranean basin, and their progressive geographical dispersal (Koukouras et al 2010). In addition to the presently observed warming of the western basin, the changes in the main current circulation in the Mediterranean during the last few decades may also explain the recent spread of Red Sea species towards the western basin (see Francour et al 2010, Otero et al 2013.…”
mentioning
confidence: 91%